Các yếu tố ảnh hưởng đến quyết định lựa chọn điểm đến của khách du lịch: Trường hợp điểm đến TP. Hồ Chí Minh - Nguyễn Xuân Hiệp (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
This study explores and measures the factors affecting tourists’ decision to choose Ho Chi Minh City as their destination, using both qualitative and quantitative methods. The survey data covering October 2015–February 2016 are collected from 615 domestic and international tourists, who have paid a visit to the city before. Additionally, the quantitative model based on previous studies is tested by Structural Equation Modelling (SEM). The results indicate that the determinants of the decision made by these tourists include travel motivation, destination image, and destination information source. Among them the source of information on the destination is found to affect the travel motivation, which, in turn, strongly affects the destination image.